2012
DOI: 10.1194/jlr.m018887
|View full text |Cite
|
Sign up to set email alerts
|

Murine bone marrow-derived macrophages differentiated with GM-CSF become foam cells by PI3Kγ-dependent fluid-phase pinocytosis of native LDL

Abstract: This article is available online at http://www.jlr.org Supplementary key words atherosclerosis • cholesterol • granulocytemacrophage colony-stimulating factor • phosphoinositide 3-kinase • low density lipoprotein Development of atherosclerotic plaques results from the accumulation of cholesterol within arterial vessel walls. Macrophages play a critical role in this process by mediating uptake of the cholesterol-rich particle LDL, resulting in arterial accumulation of cholesterol. LDL uptake by macrophages is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…Previous studies on the importance of macropinocytosis were restricted to LDL [5, 6, 24, 25] but we found that this also extends to modified LDL [7]. Overall, our studies demonstrate that PI3K is important for both receptor-mediated uptake processes and macropinocytosis, and confirms links that were identified in some previous studies [5, 6, 2426]. …”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on the importance of macropinocytosis were restricted to LDL [5, 6, 24, 25] but we found that this also extends to modified LDL [7]. Overall, our studies demonstrate that PI3K is important for both receptor-mediated uptake processes and macropinocytosis, and confirms links that were identified in some previous studies [5, 6, 2426]. …”
Section: Discussionsupporting
confidence: 90%
“…This PI3Kg-dependant infiltration can be initiated by chemokine or matrix extracellular degradation product such as elastin peptides which activate a elastin complex receptor expressed at the surface of immune cells able to recruit PI3Kg . Moreover, the work of Anzinger et al demonstrated that GMeCSFedifferentiated murine macrophages become foam cells by fluid-phase pinocytosis of LDL and identified PI3Kg as contributing to this process (Anzinger et al, 2012). Together these results, reinforced further by others , prove that targeting the PI3Kg isoform in this pathological context is of great interest.…”
Section: C2-a Endothelial Cellmentioning
confidence: 82%
“…Bone marrow isolation was performed as described previously 12. The bone marrow cells were differentiated into BMDMs with macrophage colony-stimulating factor (M-CSF) (Peprotech, Rocky Hill, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%